Quality and Sensory Attributes of Tumbled or Marinated Beef Jerky - Ashton L. McGinn; D. L. Boyle; Travis G. O'Quinn; Elizabeth A. Boyle (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: The objective of this research was to evaluate the quality and sensory characteristics of vacuum-packaged shelf-stable beef jerky produced using tumbling or marination. Study Description: This study used 12 USDA Select beef inside top rounds (semimembranosus) that were stored in a non-barrier shrink bag held at 36°F for 10 to 14 days before processing. On each processing day, whole rounds were trimmed, pH was measured, and the weights were obtained before and after trimming. Trimmed rounds were cut in half, and each half was allocated to a tumbled or marinated treatment. Before the processing treatments were applied, each beef round half was sliced using a slicer (Treif Puma Slicer, Shelton, CT) into 3 mm slices and then weighed. Pieces from each half were collected for determination of structural analysis, sarcomere length (SL), and myofiber diameter (MD) using transmission electron microscopy (TEM) and light microscopy (LM) and for proximate analysis. After tumbling or marinating, percent pickup was measured following a 5-minute rest period, and a sample from each half of tumbled or marinated rounds was held to measure sodium chloride content (SCC), structural analysis, SL, and MD. After thermal processing, samples from each treatment were vacuum-packaged and sampled initially on day 0 and after 3 and 6 months at 68°F. Cook yield was determined after thermal processing. On day 0, the pH, moisture, and protein content, water activity (aw), instrumental color, shear force (SF), sensory evaluation, SCC, structural analysis, SL, and MD were measured. After 3 and 6 months of storage, the instrumental color, sensory evaluation, aw, SF, SCC, moisture, structural analysis, SL, and MD were measured. The Bottom Line: Tumbling produced a jerky product that was more tender, less brittle, and more flavorful during 6 months of storage compared to marination as a processing method.
Keywords: beef jerky; tumbling; marination